2021
DOI: 10.3389/fonc.2021.784457
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Radiation and Chemoradiation Therapy on the Head and Neck Mucosal Microbiome: A Review

Abstract: Radiation (RT) and chemoradiation therapy (CRT) play an essential role in head and neck cancer treatment. However, both cause numerous side effects in the oral cavity, paranasal sinuses, and pharynx, having deleterious consequences on patients’ quality of life. Concomitant with significant advances in radiation oncology, much attention has turned to understanding the role of the microbiome in the pathogenesis of treatment-induced tissue toxicity, to ultimately explore microbiome manipulation as a therapeutic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 80 publications
(137 reference statements)
4
22
0
Order By: Relevance
“…In addition to C. albicans, the other microbial species found most commonly by percentage contribution during radiotherapy were F. nucleatum subspecies nucleatum, V. parvula and S. epidermidis. Other studies have reported changes in microbial oral flora in patients with oral carcinomas (Martin and van Saene, 1992;Nagy et al, 1998;Anjali et al, 2020) and during radiation treatment (Llory et al, 1972;Brown et al, 1975;Keene et al, 1981;Keene and Fleming, 1987;Epstein et al, 1991;Abu Shara et al, 1993;Leung et al, 2001;Vissink et al, 2003b;Dahlen et al, 2009;Anjali et al, 2020;Zagury-Orly et al, 2021). These changes have also included an increase in Fusobacterium and Veillonella (Nagy et al, 1998;McIlvanna et al, 2021;Minarovits et al, 2021), as was found in this study.…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…In addition to C. albicans, the other microbial species found most commonly by percentage contribution during radiotherapy were F. nucleatum subspecies nucleatum, V. parvula and S. epidermidis. Other studies have reported changes in microbial oral flora in patients with oral carcinomas (Martin and van Saene, 1992;Nagy et al, 1998;Anjali et al, 2020) and during radiation treatment (Llory et al, 1972;Brown et al, 1975;Keene et al, 1981;Keene and Fleming, 1987;Epstein et al, 1991;Abu Shara et al, 1993;Leung et al, 2001;Vissink et al, 2003b;Dahlen et al, 2009;Anjali et al, 2020;Zagury-Orly et al, 2021). These changes have also included an increase in Fusobacterium and Veillonella (Nagy et al, 1998;McIlvanna et al, 2021;Minarovits et al, 2021), as was found in this study.…”
Section: Discussionsupporting
confidence: 67%
“…Microbial colonisation increased dramatically during radiotherapy and also during the palliative care phase of treatment for patients prior to their death. Significant increases in microbial numbers during radiotherapy have been reported previously (Abu Shara et al, 1993;Vissink et al, 2003b;Belazi et al, 2004;Zagury-Orly et al, 2021). It was also found that all patients undergoing radiotherapy who had C. albicans colonisation exceeding 1x10 5 colonies per swab after 1 week of radiotherapy subsequently required at least antifungal treatment to manage oral complications of head and neck radiotherapy; some required hospitalisation.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations